The Effect of Return on Assets, Current Ratio, Debt to Equity Ratio, and Price Earning Ratio on Profit Growth in Cosmetic Companies Listed on The Indonesia Stock Exchange in The Period 2017-2022 - Christianty, Restia; Turukay , Evracia (Sean Institute, 2025)
The study was conducted on cosmetic companies listed on the Indonesia Stock Exchange for the period 2017 - 2022 with the aim of assessing whether Return On Assets, Current Ratio, Debt To Equity Ratio, and Price Earning Ratio have a partial effect on profit growth. The respondent selection technique in this study was the purposive sampling technique, from a population of 8 companies, 5 companies were produced as samples that met the criteria.The data analysis technique used in this study is multiple linear regression analysis to measure the influence of independent variables on dependent variables. The results of the data analysis show thatReturn On Asset has a positive and significant effect on profit growth because the T-calculation value is greater than the T-table value and the significance value is less than 0.05, Current Ratio has a positive and insignificant effect on profit growth because the T-calculation value is less than the T-table value and the significance value is greater than 0.05, Debt To Equity Ratio has a negative and insignificant effect on profit growth because the T-calculation value is less than the T-table value and the significance value is greater than 0.05, and Price Earning Ratio has a negative and significant effect on profit growth because the T-calculation value is greater than the T-table value and the significance value is less than 0.05.